Comparison of vacuum assisted closure therapy with conventional dressing in the management of necrotizing fasciitis wound - Kumar, Birbal; Mohil, R. S.; Mohan, Sajith K.; Bhardwaj, Navnik Singh; Pasricha, Arush; Singh, Kashinath; Garg, Raghav; Namdeo, Ratnakar (International Surgery Journal, 2021)
Background: The purpose of our study was to compare the effect of vacuum assisted closure (VAC) therapy and conventional dressings in patients with open wounds due to necrotizing fasciitis (NF) on the basis of healing rate, infection control, frequency of dressing and pain score. Methods: The study evaluated 50 patients admitted with NF requiring surgery over a period of 18 months. The patients were randomized to two groups. In group A patients, the wounds were managed with conventional dressings and in group B patients, negative pressure wound therapy (NPWT) was applied. Serial assessment of both groups was done for four weeks. The parameters including size of wound, wound bed, granulation tissue formation, color, amount and odor of exudate, edema, frequency of dressing, re-debridement and pain were monitored and analysed. Results: In our study, patients with NF wounds who underwent VAC therapy had earlier granulation tissue formation, resolution of infection and readiness for skin grafting. The frequency of dressing, requirement of re-debridement, resolution of edema, odor, skin maceration, inflammation around wound and pain significantly reduced in group B (VAC) when compared to conventional dressing group. Conclusions: When compared to the conventional dressing on NF wound, application of VAC helped in early appearance of granulation tissue, significant reduction of inflammation, wound odor, exudate, need for re-debridement, frequency of dressing and pain. Thus, VAC dressing can be considered as a better option in the management of NF wounds.